STRATEGI IMITASI DAN MANAJEMEN PENGETAHUAN DALAM PENGEMBANGAN INOVASI PLA (POLY LACTIC ACID) PADA AGROINDUSTRIKEMASAN BIODEGRADABEL DI INDONESIA - Fitry Filianty (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2013)
Indonesia has the potential for development of PLA (Poly Lactic Acid) as biodegradablepackaging agroindustry due to the availability of raw material, such as tubers as a source ofstarch and lignocellulose as a source of cellulose, but Indonesia has limitations in terms of itstechnology. This was due to the intensity and quality of the research that has not beenadequate. For that condition, imitation strategies can be developed for PLA (Poly Lactic Acid)agroindustry in Indonesia and the level of product imitation strategies is knockoff or cloning.At that level, PLA agroindustry to be developed completely replicate existing products but haveother brands. With this strategy, the PLA agroindustry is expected to produce a cheaper priceproduct because of the availability of raw materials in Indonesia that easy to fine. Rawmaterial for PLA that can be selected from cassava tubers beacause its easy in cultivation andcheaper among other types of bulbs. To improve competitiveness, the company who built theimitation strategy needs to be managed with the application of knowledge management inorder to be able to last long existence.